Sleep, health perception and physical activity in university adolescents Sono, percepção de saúde e atividade física em adolescentes universitários - Andrade R.D.* (2017)
© 2017, Nucleo de Estudos da Saude do Adolescente. All rights reserved.Objective: This study aimed to analyze sleep and physical activity indicators according to self-reported health in university adolescents. Methods: 84 adolescents participated in the study with ages between 17-21 years (52.4% boys), who answered questionnaires with inquiries about sleep, physical activity and self-reported health. Results: The average sleep duration was 7.2 (1.4) hours and 56.3% were classified as insufficiently active. Among the adolescents surveyed, 57.8% and 28.9% have good and excellent perception of their health, respectively, only 13.3% perceived it as regular. Academics with longer sleep duration showed more positive perception of their health (p=0.010), as well as those with more time devoted to vigorous physical activity (p=0.002). Nonetheless, sleep duration and time of physical activity, moderate (p=0.902) or vigorous (p=0.738), were not correlated. Conclusion: Sleep duration and length of physical activity are important factors for a positive self-reported health. However, both variables have complex relationships that could not be explained by direct correlations. Moreover, vigorous physical activity seems to be more relevant to a positive perception of health.